Facile Strategy on Hydrophilic Modification of Poly(ε-caprolactone) Scaffolds for Assisting Tissue-Engineered Meniscus Constructs In Vitro - Zhou, Zhu-Xing; Chen, You-Rong; Zhang, Ji-Ying; Jiang, Dong; Yuan, Fu-Zhen; Mao, Zi-Mu; Yang, Fei; Jiang, Wen-Bo; Wang, Xing; Yu, Jia-Kuo (Frontiers in Pharmacology, 2020)
Poly (ε-caprolactone) (PCL) derived scaffolds, originating from their good biosafety and biomechanical performances, have been extensively explored in the field of tissue-engineered meniscus (TEM). However, the poor intrinsic hydrophobicity severely hindered their wide applications for the scaffold-assisted tissue regeneration. Herein, we developed a simple strategy on surface modification of three-dimensional (3D) PCL scaffolds via a simply soaking treatment of sodium hydroxide (NaOH) solutions to increase the hydrophilicity and roughness of scaffolds’ surface. We investigated the effect of hydrolysis degree mediated by NaOH solutions on mechanical properties of 3D scaffolds, considering the importance of scaffolds’ resistance to internal force. We also investigated and analyzed the biological performances of mesenchymal stromal cells (MSCs) and meniscal fibrocartilage cells (MFCs) onto the scaffolds treated or untreated by NaOH solutions. The results indicated that hydrophilic modification could improve the proliferation and attachment of cells on the scaffolds. After careful screening process condition, structural fabrication and performance optimization, these modified PCL scaffolds possessed roughened surfaces with inherent hierarchical pores, enhanced hydrophilicity and preferable biological performances, thus exhibiting the favorable advantages on the proliferation and adhesion of seed cells for tissue-engineered meniscus. Therefore, this feasible hydrophilic modification method is not only beneficial to promote more smart biomedical scaffold materials but also show great application prospect in tissue engineering meniscus with tunable architectures and desired functionalities.